Substance-related exogenous psychosis: a postmodern syndrome - Martinotti, Giovanni; De Risio, Luisa; Vannini, Chiara; Schifano, Fabrizio; Pettorruso, Mauro; Di Giannantonio, Massimo (CNS spectrums, 2021)
There is growing recognition that substance use is associated with the emergence of psychosis.Elements of post-modernity dominate contemporary social contexts and operate as existential background factors that contribute to the emergence of substance-related psychotic phenomena, particularly use of potent and highly rewarding novel psychoactive substances (NPS). About 25% of first-episode psychoses are substance-induced (SIP). DSM-5 SIP diagnosis is based on the assumption that symptoms are transient and disappear after sustained abstinence. This narrowed definition does not consider the issue of persistent SIP. There is a clear need for a new diagnostic framework that provides reliable, unambiguous clinical criteria to differentiate between comorbid conditions (i.e., schizophrenia patients with a substance use disorder) and substance-related psychoses. In the present contribution, we aim to outline a novel and separate clinical entity: substancerelated exogenous psychosis (SREP). Within this diagnostic category, we refer to both transientand persistent psychoses associated with substance use. SREP is conceived as a distinct psychoticdisorder with psychopathological specificities that clearly differentiate it from schizophrenia. We address differences in terms of clinical presentation, epidemiology, etiological models and treatment response. SREP is characterized by altered states of consciousness, persecutory delusions, visual and cenesthetic hallucinations, impulsivity and psychomotor agitation, affectiveand negative symptoms, a pervasive feeling of unreality and intact insight. Delusions are typically secondary to abnormal perception resulting from a characteristic “sensorialization” of the world. Longitudinal studies are warranted to substantiate our hypothesis of a novel diagnostic categoryand support the clinical validity of SREP. This may have important implications in terms of early differential diagnosis and staging (i.e., between comorbid conditions, persistent and transientsubstance-related psychotic states) as well as choice of treatment interventions.